Determining the Role of Serum Cystatin C in the Early Detection of Contrast-Induced Nephropathy after Coronary Intervention - F. J. Al-Tu’ma; M. H. Dheyauldeen; M. A. Al-Mukhtar; S. Y. Al-Jawad; R. M. Al-Saegh (New Horizons in Medicine and Medical Research Vol. 12, 2022)
The most common complication of both coronary angiography (CAG) and percutaneous coronary intervention (PCI) is Contrast induced nephropathy (CIN). The aim of present study is to assess whether serum cystatin C could be used in diagnosis of CIN in patients undergoing elective CAG and/or PCI, 24 hours after the procedures. Eighty elective cardiology patients were involved in the study (48 males, 32 females). The research was carried out in the cardiac catheterization unit of the Al-Hussein Medical City/ Karbala Health Directorate in Holy Karbala, Iraq. Clinical examination and laboratory investigations include serum creatinine, blood urea, estimated GFR and serum cystatin C. Contrast-induced nephropathy occurred in 19 individuals (23.8%) with renal impairment ranging from grade 0 to 2. After 24 hours of angiography/angioplasty procedures, serum creatinine, cystatin C, and eGFR all increased significantly (p<0.001, 0.01 respectively). Receiver-operating characteristic analysis showed a higher area under the curve for creatinine 0.805 (95% CI=0.688, 0.921) p=0.001, 78.9% sensitivity and 60.7% specificity than serum cystatin C 0.777 (95% CI=0.673-0.881) P=0.001 sensitivity=78.9% and specificity=64%, a cutoff level of cystatin C>7 ng/ml. Cystatin C was a good biomarker for earlier diagnosis of contrast induced nephropathy.